Unpacking the role of volunteered geographic information in disaster management: focus on data quality - Marina Tavra; Anka Lisec; Morena Galešić Divić; Vlado Cetl (Geomatics, Natural Hazards & Risk)
The increasing occurrence of disasters worldwide has motivated researchers to continuously evaluate potential technological advances to support disaster management (DM) as well as emergency response. The advent of Volunteered Geographic Information (VGI) offers the possibility of near real-time data collection or the possibility of massive disaster and post-disaster data collection. VGI is a type of geographic information provided by volunteers who have no formal training in geoinformatics and geographic information systems (GIS). The objective of this review aimed to examine research publications that address VGI in the context of DM, focusing on VGI data quality. From the collected metadata of publications published in the Web of Science (WoS) on crowdsourcing and VGI in the context of DM, we extracted and processed those articles related to data quality using the text mining method and a bibliometric approach. The research addresses the quality of VGI data and its fit for purpose for DM studies that rely on accurate and reliable geographic information for successful management through identified topics. The article concludes by highlighting the potential of VGI to provide valuable information for DM, while also pointing to the need for further research to identify and improve the quality of VGI data.